Association between physical activity and depression with body dysmorphic disorder among UTAR undergraduate students - Phua, Jia Ying (2023)
Body dysmorphic disorder (BDD) is a commonly underrecognized body image disorder that is associated with high occurrence of delusional symptoms and suicidal action. Recently, BDD is shown to have an increasing prevalence among university students, with observed depressive symptoms. On the other hand, physical activity is proven to be effective in treating depressive symptoms. Therefore, a cross-sectional study was conducted to study the association between physical activity and depression with BDD among Universiti Tunku Abdul Rahman (UTAR) undergraduate students. In this study, validated questionnaires such as Body Image Disturbance Questionnaire (BIDQ), International Physical Activity Questionnaire - Short Form (IPAQ-SF), and Depression, Anxiety and Stress Scale - 21 Items (DASS-21) were used. Data was collected physically. In terms of statistical analysis, descriptive analysis was used, and the data were expressed as frequency and percentage. In addition, Chi square test was used to determine association between physical activity and depression with BDD. A total of 106 respondents has been participated in the study, with the inclusion of 70 females (66%), and 36 males (34%). Based on the results, the prevalence of BDD among UTAR undergraduate students was 4.7%, while depression prevalence was 43.3%. Most of the students were physically active, with a percentage of 58.5%. The major body area of concern included skin (26.8%), body size (25.3%) and hair (15.3%). This study found a significant association between depression and BDD (p < 0.001). However, there was no association between physical activity and BDD (p = 0.896). In conclusion, a significant association was found between depression and BDD. Future studies should be conducted to study how depression can affect BDD to provide references for more effective intervention in preventing BDD in the future.